Commenting on medieval chronicles: Between fiction and truth (on the material of the “History of Spain”, 13th century) - I. V. Ershova (Шаги)
The present article is devoted to the problem of commenting on medieval chronicles (on the example of the Old Spanish Estoria de España by Alfonso X the Wise, 13th с.) and the need not only to search for the sources of certain large and small stories, but also to explain the choice of words, naming, and the mechanism of putting together various stories from the point of view of the problem of truth/fiction (verdad / fabula) in the perception of the medieval chronicler, for whom an important goal is to present his story as truth and to make it compelling for the listener and reader. As an example, we examine the well-known chronicle story about the genealogy of the Huns (Jordan, St. Jerome, Sigebert of Gembloux), refined and edited by the editors of the Spanish chronicle, as well as two etiological legends about the origin of significant toponyms and the founding of the most important cities of Spain (the legend of the marriage of Liberia, daughter of Span; the legend of King Rocas). The studied stories have shown that the task of creating a reliable story is achieved either by deliberately creating a new, unknown narrative (the stories of Liberia and Rocas) without a clearly identifiable source, or by consciously clarifying and changing traditional information (satyrs as progenitors of the Huns).